2019 IEEE 19th International Conference on Bioinformatics and Bioengineering (BIBE) 2019
DOI: 10.1109/bibe.2019.00044
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Modeling of Ebola Propagation

Abstract: The Ebola virus disease (EVD) epidemic that occurred in West Africa between 2014-16 resulted in over 28,000 cases and 11,000 deaths -one of the deadliest to date. A generalized model of the spatiotemporal progression of EVD for Liberia, Guinea, and Sierra Leone in 2014-16 remains elusive. There is also a disconnect in the literature on which interventions are most effective in curbing disease progression. To solve these two key issues, we designed a hybrid agent-based and compartmental model that switches from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…This is necessary for mainstreaming the concept proposed in the study. An interesting SIR model, based on EBOV, combining agentbased and compartmental models, has been presented [5]. The authors suggested that the hybrid model can switch from one paradigm to another on a stochastic threshold.…”
Section: The Ebola Virus (Ebov) and Ebola Virus Diseases (Evd)mentioning
confidence: 99%
See 2 more Smart Citations
“…This is necessary for mainstreaming the concept proposed in the study. An interesting SIR model, based on EBOV, combining agentbased and compartmental models, has been presented [5]. The authors suggested that the hybrid model can switch from one paradigm to another on a stochastic threshold.…”
Section: The Ebola Virus (Ebov) and Ebola Virus Diseases (Evd)mentioning
confidence: 99%
“…SEIR-based models designed for EVD have been proposed in the literature to monitor both direct and indirect propagation of the disease in the affected population [45] and [5]. This study adopts and adapts two relevant models from the existing SEIR models by identifying and adding new compartments perceived as omitted.…”
Section: Sir Model Of Eosamentioning
confidence: 99%
See 1 more Smart Citation
“…The mathematical model of the procedure above follows: update of Susceptible (S), Infected (I), Hospitalized (H), Exposed (E), Vaccinated (V), Recovered (R), Funeral (F), Quarantine (Q), and Dead (D) is governed by a system of ordinary differential equations derived based on those in 29 , 30 . Differential calculus is a branch of calculus which in turn is a branch in mathematics.…”
Section: Overview Of Eosa and Review Of Related Studiesmentioning
confidence: 99%
“…Over the last 20 years, many different viruses have spread through different countries via airport networks. One of the well-known cases was the 2014 Ebola outbreak, which started in West Africa and caused more than 11,000 deaths worldwide ( Bailey et al, 2018 ; Tanade et al, 2019 ). Another notable case was the H1N1 virus, which was initiated in 2009 in Mexico and proceeded to spread in more than 70 countries, causing nearly 650,000 deaths between 2009 and 2010 ( Marziano et al, 2017 ; Ng et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%